Management of innovative projects at the enterprise: key concepts and features - O. A. Zyablikova (Publishing House of the State University of Management, 2021)
The course of modernization and innovative development proclaimed by the country's leadership stimulates the innovation process at enterprises. However, being engaged in the development and implementation of innovative projects in the activities of the enterprise, management of enterprises is faced with some barriers caused by the specific features of such projects. The article analyses the current state of affairs in the management of innovative development of the agro-industrial complex of the Penza region. The paper determines the existing problems and prospects in the management system of innovative projects in the specified area. The study carries out an assessment of the innovative potential of agricultural organizations of the Penza region. The authors propose a model for managing innovative projects based on a systematic approach, substantiate the application of the differential method in determining the strategy of innovative development, describe operating models for each type of strategy.